Apprehending the Pandemic - Bhowmick Gogoi, Sneha (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
People over eras have seen war, pandemics and many more, with high death and high birth rates, and multiple ups and down in the graph of demographic transitions. But at the stage of ultra-advancement of technology, facing the pandemic, the entire population needs to get conscious about the cause and consequences of population growth and its results. Thus, this is a generalized study over the present situation of covid-19 pandemic and its relation to the theoretical understanding on population, and the relation of technological advancement and education.
Keywords: Pandemic; population; death rate; mental health